2008
DOI: 10.1038/labinvest.2008.89
|View full text |Cite
|
Sign up to set email alerts
|

Integrins mediate adhesion of medulloblastoma cells to tenascin and activate pathways associated with survival and proliferation

Abstract: Medulloblastoma spreads by leptomeningeal dissemination rather than by infiltration that characterizes other CNS tumors, eg, gliomas. This study represents an initial attempt to identify both the molecules that mediate medulloblastoma adhesion to leptomeninges and the pathways that are key to survival and proliferation of tumor following adhesion. As a first step in molecule identification, we produced adhesion of D283 medulloblastoma cells to the extracellular matrix (ECM) of H4 glioma cells in vitro. Within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 55 publications
(74 reference statements)
0
33
1
2
Order By: Relevance
“…It was shown that ITGA9 is expressed in melanoma cells, 27 aberrantly upregulated in small-cell lung cancers, both cell lines and primary tumors 28 and medulloblastoma cells, 29 the expression level of integrin a9b1 on astrocytomas is correlated with increased grade of this brain tumor and is highest on glioblastoma, whereas normal astrocytes do not express this integrin, 30 ITGA9 is absent in normal adults colon tissues but it is expressed in 6 of 10 primary colon adenocarcinomas and 2 of 7 colon adenocarcinoma cell lines (Caco-2 and T84). 31 According to another study, ITGA9 has significantly higher expression levels in colorectal tumors with high microsatellite instability ( mechanisms of ITGA9 activation in cancer cells remain unclear; however the effect may unfavorably contribute to the cancer prognosis supporting ITGA9 as a potential target for anti-integrin therapy.…”
Section: Integrin Alpha9 (Itga9) Expression and Epigenetic Silencing mentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that ITGA9 is expressed in melanoma cells, 27 aberrantly upregulated in small-cell lung cancers, both cell lines and primary tumors 28 and medulloblastoma cells, 29 the expression level of integrin a9b1 on astrocytomas is correlated with increased grade of this brain tumor and is highest on glioblastoma, whereas normal astrocytes do not express this integrin, 30 ITGA9 is absent in normal adults colon tissues but it is expressed in 6 of 10 primary colon adenocarcinomas and 2 of 7 colon adenocarcinoma cell lines (Caco-2 and T84). 31 According to another study, ITGA9 has significantly higher expression levels in colorectal tumors with high microsatellite instability ( mechanisms of ITGA9 activation in cancer cells remain unclear; however the effect may unfavorably contribute to the cancer prognosis supporting ITGA9 as a potential target for anti-integrin therapy.…”
Section: Integrin Alpha9 (Itga9) Expression and Epigenetic Silencing mentioning
confidence: 99%
“…37 Here, two different aspects of the changes are to be discussed. From the one side, an activation of ITGA9 expression was shown for different human tumors and cancer cells-smallcell lung cancer, 28 medulloblastoma cells, 29 astrocytomas and glioblastoma. 30 From the other side, frequent genetic/epigenetic aberrations (deletions, methylation) of ITGA9 were identified in different epithelial cancers using NotI-microarray.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…physiologic processes such as embryogenesis and wound healing, but it is also an integral characteristic in pathological conditions such as cancer metastasis (1)(2)(3)(4)(5)(6)(7)(8). Cell motility itself has been studied in a variety of organisms to create a general model.…”
mentioning
confidence: 99%
“…Focal adhesion kinase (FAK) 2 acts as a signaling node at cell adhesion sites called focal contacts to promote cytoskeletal reorganization, adhesion, migration, and survival (11). FAK regulates cell motility through integrins and growth factor receptors (11) by relaying cues from the extracellular matrix through the plasma membrane, and into the cytoplasm.…”
mentioning
confidence: 99%
“…There are few theories to explain this phenomenon. Fiorilli et al 7 in 2008 described some medulloblastoma molecular features that can help our understanding in this matter. He described increased expression levels of integrins and tenascins in the medulloblatoma cells.…”
Section: Discussionmentioning
confidence: 99%